2009
DOI: 10.1111/j.1444-0938.2009.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

A medical device/drug delivery system for treatment of glaucoma

Abstract: Background:The aim of this study was to investigate the uptake and release kinetics of two common glaucoma drugs delivered onto hydrogel contact lenses using analytical chemistry and to evaluate this device's ability to control intraocular pressure in a limited number of volunteers. Methods: Contact lenses were incubated in a source solution containing timolol maleate or brimonidine tartrate to determine uptake kinetics. The lenses were then immersed in fresh saline to determine release kinetics. Analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 19 publications
(23 reference statements)
1
38
0
Order By: Relevance
“…The control contact lens treatment decreased the IOP more significantly than eye drops by 0.88 ± 0.28 mmHg (p = 0.0294), despite the sixfold lower drug dosing compared to eye drops ( Table 1). The result was consistent with other in vivo [19,20,[46][47][48][49] and modeling studies [9] that showed the drug delivery by contact lens could provide a higher bioavailability. Similarly, the therapy from vitamin E modified contact lens lowered IOP during lens wear by comparable magnitude as eye drops but with 4-fold lower drug loading.…”
Section: Therapeutic Efficacy and Safety Evaluationsupporting
confidence: 94%
“…The control contact lens treatment decreased the IOP more significantly than eye drops by 0.88 ± 0.28 mmHg (p = 0.0294), despite the sixfold lower drug dosing compared to eye drops ( Table 1). The result was consistent with other in vivo [19,20,[46][47][48][49] and modeling studies [9] that showed the drug delivery by contact lens could provide a higher bioavailability. Similarly, the therapy from vitamin E modified contact lens lowered IOP during lens wear by comparable magnitude as eye drops but with 4-fold lower drug loading.…”
Section: Therapeutic Efficacy and Safety Evaluationsupporting
confidence: 94%
“…Biodegradable PLA nanoparticles (140 nm) administered intravitreally have been shown to localize in the retinal pigment epithelium (51), and coating nanoparticles with polyethylene glycol (PEG) has been reported to enhance the therapeutic efficacy of treatment for ocular diseases such as autoimmune uveoretinitis (52). Drug-impregnated contact lenses have been widely investigated for the sustained release of ocular drugs (53)(54)(55). Soft contact lenses are typically composed of nonbiodegradable hydrogels of poly(2-hydroxyethylmethacrylate) (PHEMA) or hydroxyethylmethacrylate (HEMA) copolymerized with other monomers such as methacrylic acid, acetone acrylamide, and vinyl pyrrolidone.…”
Section: Examples Of Biodegradable Ocular Drug Delivery Systemsmentioning
confidence: 99%
“…2A). Given that previous studies have shown the delivery of biologicals and therapeutic agents to the ocular surface by CLs, 38,39 we sought to determine whether lenses could be coated with VN. Lotrafilcon A CLs were incubated in sera from patients with LSCD for 10 days before they were placed in PBS for an additional 7 days.…”
Section: Vitronectin Is Adsorbed and Released From Clsmentioning
confidence: 99%